The effect of nurse-led empowering education on nutrition impact side effects in patients with colorectal cancer undergoing chemotherapy: A randomised trial - Tuominen Leena; Ritmala Marita; Vahlberg Tero; Mäkelä Siru; Nikander Pia; Leino-Kilpi Helena (Elsevier, 2025)
Objective: This study assessed the effect of empowering education on patient-reported outcomes and morbidity.
Methods: A randomised controlled trial was conducted on adults with colorectal cancer (43 + 40). The intervention consisted of one-hour empowering patient education on nutrition impact side effects. The effect was compared with standard care. The difference between the groups was analysed pre and post intervention.
Results: The change in malnutrition-related knowledge level was higher in the intervention group compared to control group (median 0.0, IQR 1.00 vs median 0.0, IQR 0.0, p = 0.028). Additional contacts with outpatient clinic were fewer in intervention group (median 0.00, IQR 0.00) compared to control group (median 1.00, IQR 2.00, p < 0.001). We did not find a statistically significant difference in the change in activation level, risk of malnutrition and quality of life between the groups.
Conclusion: Empowering education may affect positively on patients' knowledge level related to malnutrition and reduce the number of additional contacts with health care thus reduce health care costs.
Practice implications: Empowering education may be used in patients with colorectal cancer to improve knowledge and reduce additional contacts with health care. Further research is needed on the effect of empowering education in self-care.